Combined metabolome and transcriptome analysis reveal the mechanism of water stress in Ophiocordyceps sinensis - Li He; ChuanYong Li; ZhaoHe Chen; YanLi Huo; Bo Zhou; Fang Xie (BMC Genomics)
Abstract Background Ophiocordyceps sinensis (O. sinensis) is the dominant bacterium in the asexual stage of Chinese cordyceps, and its growth usually suffers from water stress. Thus, simulating its ecological growth environment is crucial for artificial cultivation. This study aimed to reveal the mechanism underlying the water stress tolerance of Ophiocordyceps sinensis (O. sinensis) by combining metabolomic and transcriptome analyses to identify crucial pathways related to differentially expressed genes (DEGs) and metabolites (DEMs) involved in the response to water stress. Results Gene coexpression analysis revealed that many genes related to ‘betalain biosynthesis’, ‘tyrosine metabolism’, ‘linoleic acid metabolism’, ‘fructose and mannose metabolism’, and ‘starch and sucrose metabolism’ were highly upregulated after 20d-water stress. Metabolomic analysis revealed that many metabolites regulated by these genes in these metabolic pathways were markedly decreased. On the one hand, we surmised that carbohydrate metabolism and the β-oxidation pathway worked cooperatively to generate enough acyl-CoA and then entered the TCA cycle to provide energy when exposed to water stress. On the other hand, the betalain biosynthesis and tyrosine metabolism pathway might play crucial roles in response to water stress in O. sinensis by enhancing cell osmotic potential and producing osmoregulatory substances (betaine) and antioxidant pigments (eumelanin). Conclusions Overall, our findings provide important information for further exploration of the mechanism underlying the water stress tolerance of O. sinensis for the industrialization of artificial cultivation of Chinese cordyceps.